Assessing the impact of new technologies on wages and labour income shares - Mahdi Ghodsi; Robert Stehrer; Antea Barišić (The Vienna Institute for International Economic Studies (wiiw), 2024)
This paper advances the literature on the impacts of new technologies on labour markets, focusing on wage and labour income shares. Using a dataset from 32 countries and 38 industries, we analyse the effects of new technologies - proxied by patents, information and communication technology (ICT) capital usage, and robot intensity - on average wages and labour income shares over time. Our results indicate a positive correlation between patents and wage levels along with a minor negative impact on labour income shares, suggesting that technology rents are not fully passed on to labour. Robot intensity is positively associated with labour income shares, while ICT capital has an insignificant effect. These effects persist over time and are reinforced by global value chain (GVC) linkages. Our conclusions align with recent research indicating that new technologies have a generally limited impact on wages and labour income shares.
Keywords: C13; C23; F14; F16; O33; 330; Robot adoption; ICT investment; new technologies; GVC; wages; labour income shares